Co-assemblies of micelle-forming diblock copolymers and enzymes on graphite substrate for an improved design of biosensor systems - Sigolaeva, Larisa V.; Pergushov, Dmitry V.; Synatschke, Christopher V.; Wolf, Andrea; Dewald, Inna; Kurochkin, Ilya N.; Fery, Andreas; Mueller, Axel H. E. (Soft Matter, 2013)
The adsorption of ionic amphiphilic diblock copolymers comprising a polycationic block, polybutadiene-block-poly(2-(dimethylamino)ethyl methacrylate) (PB-b-PDMAEMA); and its quaternized derivative (PB-b-PDMAEMAq) from aqueous media onto graphite-based surfaces was examined. Both diblock copolymers in aqueous solution form star-like micelles with a hydrophobic PB core and a cationic corona built up from either strong cationic PDMAEMAq or pH-sensitive PDMAEMA. AFM experiments show that PB-b-PDMAEMAq micelles interact slightly with a graphite surface providing films with a low surface coverage. PB-b-PDMAEMA micelles adsorbed onto a graphite surface at pH ≥ 7 result in a more homogeneous coverage of the graphite surface by the diblock copolymer. The adsorption of two enzymes, tyrosinase (Tyr) and choline oxidase (ChO) on the graphite surface premodified with these diblock copolymers was also monitored by AFM and by electrochemical measurements of the enzymatic activities of PB-b-PDMAEMA-Tyr and PB-b-PDMAEMA-ChO films. A pronounced increase in the enzymatic activity of tyrosinase was observed with the increasing concentration of PB-b-PDMAEMA micelles in solution used for their depositions. Also, a pronounced increase in the enzymatic activities of both tyrosinase and choline oxidase was observed with the increasing pH of the deposition of the micelles from 2 to 10. The enzymatic activity increases with the coverage of the graphite surface with the preadsorbed copolymer. Finally, the polymer-enzyme films were tested as biosensors for phenol (when tyrosinase was adsorbed) and choline (when choline oxidase was adsorbed) and their activity and stability were compared to already existing setups. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20